MENGENAL DIRI PADA REMAJA: SEBUAH ASPEK PENTING DALAM PSIKOEDUKASI - Riziq, Afrian; Muslimah, Alfiana Indah; Rikmasari , Rima (An-Nizam, 2024)
This research aims to have better self-understanding, better emotional management, higher self-acceptance, make more informed decisions. The benefits of knowing yourself are, understanding your strengths and weaknesses, finding your interests, increasing your self-confidence and motivation to learn. The results of data analysis showed that the level of understanding about Knowing Yourself in adolescents before psychoeducation was carried out, in the low category the percentage was (56%) and after being given psychoeducation decreased to get a percentage of (32%), then in the medium category the percentage was (32%) and after being given Psychoeducation, it decreased so that the percentage was (20%), then in the high category the percentage was (12%) and after being given socialization, it increased so that the percentage was (48%). Based on these data, it can be concluded that there has been an increase in the knowledge of teenagers in the RW 02 area of ​​Wibawamulya Village, Cibarusah Regency regarding their understanding of themselves.